On my way to Herman Melville’s Moby Dick, I found… some preliminary remarks from an unwritten book - Sievers, Burkard (Cuadernos de Administración, 2009)
Purpose: The author is revisiting the body of hismanuscripts on Herman Melville’s Moby Dick,which he began writing some 15 years ago.Though these writings have remained an‘unwritten book’, Melville’s works had a lastingimpact on his thinking and writing up to thepresent. He reveals some of the experiences andemotions concomitant with academic writing thatremain more often than not hidden from the reader. Design/methodology/approach: This paper is apersonal reminiscence on the experience ofacademic writing for about four decades. It is astory of how an academic becomes acquaintedwith and then influenced/inspired by a piece ofliterature and discovers how many organisationaltopics may be illuminated by works of literature.Findings: Even an unwritten book does notnecessarily lead to completely neglecting whathad been written. This may be a relief and an encouragement to others, who realize they arenot alone in this respect. Originality/value : Thepaper adds some further insight into the not-soobviousand broadly hidden experience of the ‘production process’ of academic writing andillustrates the relevance and importance ofliterature for further thinking on such topics asmanagement and organization